Perbedaan Pertumbuhan Bakteri Staphylococcus aureus Dengan Pemberian Perasan Daun Anting-Anting Dan Perasan Daun Bahagia - Dita Artanti; Eka Radiawati (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2020)
ABSTRACT               Gram Positive Bacteria, one of which is Staphylococcus aureus is a type of bacteria that is a major cause of nosocomial infection due to surgical procedures and treatment equipment in hospitals and poisoning in several regions in Indonesia. Staphylococcus aureus is commonly found in skin, nose, mouth, eye, finger, intestinal, and liver lesions. Juice of Anting-anting leaves (Acalyhpa indica L.) and happy leaf plants (Dieffenbachia bowmanii) are known to have medical benefits. Especially in its ability to produce metabolites that function as anti-bacterial compounds. This study aims to determine the differences in the growth of Staphylococcus aureus colonies which were given the leaves of Anting-anting and the leaves of Happy leaves. The research method uses the liquid dilution method in which the Staphylococcus aureus bacteria is incubated with the leaves of the Anting-anting and the leaves of the Happy leaves with a concentration of 100% at 37 ° C overnight. Then grown on Mannitol Salt Agar (MSA) media. The results showed that there was no difference in the growth of Staphylococcus aureus bacteria colonies that had been given the treatment of Juice of Anting-anting leaf (Acalyhpa indica L.) and happy leaf plants (Dieffenbachia bowmanii) which were marked by the absence of colony growth. So that the concentration of 100% in both leaves of juice is the best concentration that can be used to control the growth of Staphylococcus aureus.  Keywords : Anting-anting Leaves, Bahagia Leaves, Staphylococcus aureus